Neonatal phototherapy and cancer risk: a systematic review and meta-analysis - Freeman, Sloane J.; Keown-Stoneman, Charles D. G.; Ghobrial, Mariah; Jegathesan, Thivia; Sgro, Michael D. (Frontiers in Pediatrics, 2025)
ObjectiveTo evaluate the risk of cancer after phototherapy for neonatal hyperbilirubinemia.Study designThis was a systematic review and meta-analysis. Electronic databases, including PubMed, Embase, and Cochrane Library, were searched. Prospective and retrospective studies, case series, and review studies published between 1970 and 2025 were included. Studies underwent two stages of screening. The first phase was title and abstract screening. The second phase was a full-text review of studies deemed to meet the inclusion criteria. Risk of bias was assessed using ROBINS-E. Inverse-variance weighted multi-level random effects models were used for all analyses.ResultsThis systematic review and meta-analysis included 15 studies. Risk of bias was low in eight studies, one study was judged to have some concerns, and six studies were determined to have a high risk of bias. A total of 6,675,265 patient data points were included. Studies ranged from 1995–2022, with an age group from 35 weeks to 31 years old. Overall, there was an estimated 24% increased odds of cancer for those who received phototherapy compared to those who did not [OR = 1.24; 95% CI: (1.12, 1.36); p < 0.001].ConclusionsPhototherapy for neonatal hyperbilirubinemia was associated with a small increased risk of cancer up to age 31 years. This association must be balanced by the well-understood risk of Bilirubin-Induced Neurologic Dysfunction.